The Regulation of Immune Responses by DC Derived Type I IFN - Gommerman, Jennifer; Ng, Dennis (Frontiers in Immunology, 2013)
Our immune system bears the tremendous task of mounting effective anti-microbial responses whilst maintaining immunoregulatory functions to avoid autoimmunity. In order to quickly respond to pathogens, Dendritic cells (DC) are armed with pattern recognition receptors (PRRs), allowing them to recognize highly conserved pathogen-associated molecular patterns (PAMPs) that are uniquely expressed by invading microbes. PRR activation can trigger DCs to release the pleiotropic cytokine, Type I IFN, which facilitates various biological functions in different immune cell types. In this review, we will discuss the classical PRR-induced Type I IFN response in DCs as well as describe a novel mechanism for Type I IFN induction by the Tumor-Necrosis Factor receptor superfamily (TNFRSF) members, TNFR-1 and Lymphotoxin-β receptor (LTβR). While PRR activation during viral infection, produces large amounts of Type I IFN in a relative short period of time, TNFRSF-induced Type I IFN expression is modest with gradual kinetics. Type I IFN can exert pro-inflammatory effects, but in some cases it also facilitates immune-regulatory functions. Therefore, DCs are important regulators of immune responses by carefully modulating Type I IFN expression.